Signal a smart, wearable SOS and self-defense device for female commuters in Metro Manila - Catacutan, Ericka Mae D.
Commuting or using a public transportation is part of everyday life, especially for those without access for the convenience and safety of a private transportation. Unfortunately, people who commute using public transportation are often at risk of being victims of street crimes. Women are particularly at risk because these criminals often see them as easy prey. Being a female commuter myself, I was able to sympathize and relate with their concern for their own personal safety. With this, I came up with a device called "SIGNAL". SIGNAL is a smart, wearable, SOS and Self-defense device designed to effectively help defend female commuters in Metro Manila from most violent, traumatizing, and life-threatening crimes. The device is using the GPS technology as its main SOS feature, it could aid the user's rescue by sending their location to their registered contacts. It also has two self defense features that could be used either as a deterrent, a call for help, or for an immediate defense. The device is strategically designed to be flexible and convenient enough to be used in different situations, with minimal movement, while commuting. SIGNAL, an SOS and Self-Defense device, hopes to lower the probability of violent-crime victims among female commuters in Metro Manila, and help them regain their confidence in their independence and sense of security.